Implementation of the National Land Information Management System (SIMTANAS) at the Kupang City Land Agency - KOAMESA, Jemy; TODA, Hendrik; NIGA, Jacoba D; MAU, Alfred Omri Ena (Journal of Governance, Taxation and Auditing, 2023)
In an effort to change the pattern of serving the public, the National Land Agency, especially in the Kupang City Land Agency, has been providing computer-based services since 1997. Land Office Computerization (KKP) or Land Office Computerization (LOC) creates orderly land administration, improving the quality of land information. Case studies in the field, the informants in this study are employees who work in the Head of General Affairs and Personnel Affairs, Head of Land Measurement and Mapping Sub-section, Plan and Budget Compilation Officer, and Land Infrastructure Officer. Next, the researcher will carry out the stages of data collection according to Creswell as qualitative observation, qualitative interviews, qualitative documents search and qualitative audio and visual material and visual materials). The implementation model that researchers will use is the George Edward model to analyze the process of implementing the National Land Information and Management System (SIMTANAS) policy at the Kupang City Land Agency. On the side, the disposition found that SIMTANAS has only been running in its implementation in the survey, measurement and mapping sections. From the side of human resources, the budget has been fulfilled.